Marketing of Amway Products-A Study with Reference to Madurai City in Tamil Nadu - Kanthakrishnan, R. (Indian Journal of Marketing, 2006)
The objective of modern marketing is to make profits through satisfying consumers’ needs and wants. Hence, the marketers have to understand the real needs, wants, beliefs and attitudes of the consumers towards their products and services. Today, network marketing is a multi-billion dollar business. A number of companies have adopted this business model. It has grown into one of the driving forces of the 21st century economy. Network marketing is now regarded by many business leaders as the business for future. But this marketing method was misunderstood as a get-rich-quick scheme. It is also too common for network marketers worldwide to answer the legality and soundness of their business.